The role of university extension in the training teachers as multipliers of oral health (Research, Society and Development, 2020)
This paper aims to report the experience of dentistry students in a university extension project, developed with teachers from the public school system, as a way to train and motivate them to work on the oral health theme in the school context playful and interactive. This is a descriptive study, an experience report type lived by students of the Dentistry course at the Federal University of Campina Grande (UFCG), having as target audience 20 educators from daycare centers and public schools in the city of Patos / PB in 2018. The action plan of the activities sought to achieve the principle of integrality in the promotion of oral health, enabling the acquisition of basic knowledge in health with the objective of better qualifying them, to work safely with the oral health theme with children. The activities were planned based on a situational diagnosis carried out previously and didactically followed the operational model comprised of oral health discussion rounds, playful activities and workshops, evaluation of the educators' oral health conditions, in addition to evaluation meetings about the activities developed. It was observed that, after the activities were carried out, the educators felt more secure and motivated to approach the oral health theme in the classroom.